¨Comportamiento agronómico del cultivo de haba (Vicia faba L.) con diferentes dosis de abonos orgánicos más ácido húmico en el sector Chipe Hamburgo, cantón La Maná¨. - Martinez Ibarra, Yorman Dayan (2022)
This present research project was carried out at the "La Gatita" farm in the Chipe Hamburgo sector belonging to the La Maná canton, province of Cotopaxi, with a tropical climate that aims to evaluate the effect of different doses of organic fertilizers plus humic acid on the behavior agronomy of broad bean cultivation (Vicia faba L.). The research lasted 110 days from sowing to harvest, the experimental trial used in the research consists of a Random Complete Block Design (DBCA) with 24 experimental units with 15 plants per plot giving a total of 360 plants in throughout the experimental trial, the design is elaborated by three treatments and eight repetitions in the study, where five plants were evaluated for each experimental unit. The variables that were evaluated were plant height (m), days to flowering, number of pods per plant, number of grains per pod, weight of pods (g), weight of 100 fresh and dry grains (g), yield (kg/plot) and economic analysis, where five plants with different treatments were evaluated. The results of this research show that earthworm humus obtained the best results in the variables evaluated for growth, development and production in broad bean cultivation. The benefit/cost ratio in the treatment with Worm Humus obtained the best benefits with 2.33 USD.